Teacher of Tenrikyo: Reason and emotion working together ; A response paper to Professor Blackwood - Yusa, Michiko (Asian thought & society, 1991)
The author further elaborates reason and emotion in Tenrikyo religion in reply to Russell Blackwood's article in this issue of the journal. Michiko Yusa's thesis is that Tenrikyo distinguishes "negative" and "positive" emotions and ascribes reason the power to transform or purify these negative emotions into positive emotions. (DÜI-Sen)